Spatiotemporal variation of paralytic shellfish toxins in the sea area adjacent to the Changjiang River estuary. (April 2020) - Liu, Yang; Dai, Li; Chen, Zhen-Fan; Geng, Hui-Xia; Lin, Zhuo-Ru; Zhao, Yue; Zhou, Zheng-Xi; Kong, Fan-Zhou; Yu, Ren-Cheng; Zhou, Ming-Jiang
Abstract: The Changjiang (Yangtze River) River estuary (CRE) and its adjacent coastal waters is a notable region for nutrient pollution, which results in severe problems of coastal eutrophication and harmful algal blooms (HABs). The occurrence of HABs, particularly those of dinoflagellate Alexandrium spp. capable of producing paralytic shellfish toxins (PSTs), has an increasing risk of contaminating seafood and poisoning human-beings. The investigation of PSTs, however, is often hampered by the relatively low abundance of Alexandrium spp. present in seawater. In this study, a monitoring strategy of PSTs using net-concentrated phytoplankton from a large volume of seawater was employed to examine spatiotemporal variations of PSTs in the CRE and its adjacent waters every month from February to September in 2015. Toxins in concentrated phytoplankton samples were analyzed using high-performance liquid chromatography coupled with a fluorescence detector (HPLC-FLD). The results showed that PSTs could be detected in phytoplankton samples during the sampling stage in the CRE and its adjacent waters. Toxin content increased gradually from February to May, reached the peak in June, and then decreased rapidly from July to September. The maximum value of PST content was 215 nmol m −3 in June. Low-potency toxins N -sulfocarbamoyl toxins 1/2 (C1/2) were the most dominant components of PST in phytoplankton samples from February to June in 2015, while high-potency gonyautoxin 4 (GTX4) became the dominant component from July to September. Toxins were mainly detected from three regions, the sea area north to the CRE, the sea area east to the CRE, and sea area near Zhoushan Island south to the CRE. Based on the results of this study, it can be inferred that the three regions around the CRE in May and June is of high risk for PST contamination and seafood poisoning. Graphical abstract: Image 1 Highlights: A strategy on toxin study using concentrated phytoplankton applied in East China Sea. Eleven paralytic shellfish toxins were detected with HPLC during the sampling season. N -sulfocarbamoyl toxin 1/2 were dominant before June and gonyautoxins 4 after July. Three regions with high level toxins were identified around Changjiang River estuary. Toxin content exhibited unimodal variation with high level toxins in May and June. Abstract : Paralytic shellfish toxins (PSTs) in the sea area adjacent to the Changjiang River estuary were investigated to reveal the spatiotemporal variation patterns of PSTs.